2008
DOI: 10.1088/1468-6996/9/3/035003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metal-ion-to-fuel ratio on the phase formation of bioceramic phosphates synthesized by self-propagating combustion

Abstract: Synthetic calcium hydroxyapatite (HAP, Ca 10 (PO 4 ) 6 (OH) 2 ) is a well-known bioceramic material used in orthopedic and dental applications because of its excellent biocompatibility and bone-bonding ability due to its structural and compositional similarity to human bone. Here we report, for the first time, the synthesis of HAP by combustion employing tartaric acid as a fuel. Calcium nitrate is used as the source of calcium and diammonium hydrogen phosphate serves as the source of phosphate ions. Reaction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Sasikumar et al have synthesized HA using tartaric acid [12], succinic acid and citric acid [13] as fuels. It was suggested that the mentioned fuels acted as complexing agents reacting with metal cations, and prevented selective precipitation at the heating stage of solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sasikumar et al have synthesized HA using tartaric acid [12], succinic acid and citric acid [13] as fuels. It was suggested that the mentioned fuels acted as complexing agents reacting with metal cations, and prevented selective precipitation at the heating stage of solution.…”
Section: Introductionmentioning
confidence: 99%
“…It was also detected that fuel to oxidizer ratio influenced on combustion temperature. In various works [8,10,12,13,16,17] concentrated nitric acid was added in the initial solution to obtain transparent solution (without precipitates). In all cases it was not given attention to the presence of HNO 3 and its effect on the combustion process and yielded products.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the band at 961 cm −1 corresponding to the m1 vibrational mode of a phosphate group, can be observed in all spectra of CDHAP and the weak band at 473 cm −1 is attributed to the m2 vibrational mode of the phosphate group. Especially, phosphate m4 bands were observed at 633, 602 and 565 cm −1 [9, 10]. We did not observe much difference in the FTIR spectra of all CDHAPs, but a small shift in the stretching vibration of the −OH group may be due to the calcium deficiency in the HAP structure.…”
Section: Resultsmentioning
confidence: 79%
“…The shift in the major intensity peak [2 θ value 32.0/(211) plane] suggests that the calcium deficiency has occurred in HAP structure. For x = 0.3, one extra peak at a 2 θ value of 31.30 was found, indicating the formation of β‐tricalcium phosphate as an impurity [9, 10]. This clearly indicates that the structure is not stable at x = 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…Since microstructure differs from the method of preparation, various synthesis methods such as solid state reaction 8, hydrothermal 9, sol–gel 10, 11, co‐precipitation 12, flame spray pyrolysis 13, emulsion 14, mechanochemical 15, template 16, microwave 17, polymer‐assisted 18, self‐propagating combustion 19, 20, and sonochemical technique 21 have been reported for HAp synthesis. Recently, sonochemical method has been chosen to prepare a variety of nanostructured materials at room temperature.…”
Section: Introductionmentioning
confidence: 99%